Strengthening identification of high-risk animals using a novel identification approach - Porter, Sandra Paige, author; Whittier, Jack C., advisor; Morris, David L., committee member; Pedell, D. L., committee member (Colorado State University. Libraries, 2010)
The need for animal disease surveillance is a subject of constant discussion within the United States. Choosing an appropriate method of identification and trace-back that coincides with commerce is of the utmost importance. The production cycle of the imported feeder animal is fairly well defined: animals enter the U.S., are either sent to stocker or to feedlot operations, and after finishing are sent to the abattoir. The lifecycle of the imported roping animal is not clearly defined; the animals enter the U.S. and eventually the food chain, with limited knowledge of movements between importation and harvest. A novel form of animal identification utilizing retinal imaging was tested to maintain animal identification during the production cycle of both Mexican roping steers and spayed feedlot heifers. This secure and reliable method of identification combines GPS capabilities with the vascular pattern of the ocular fundus. Incorporation of this technology into a lifetime trace-back system for high risk animals that has the capability to follow animals through their production cycle to the abattoir when other forms of identification are lost. To test the ability of this technology to maintain animal identification 102 spayed feeder heifers were retinal imaged at the time of importation. The feeder heifers were verified at the feedlot and again at harvest. Nine hundred thirty five recreational animals were retinal imaged at the time of importation. Recreational animals typically have a lifespan longer than feeder cattle, and due to the scope of the research, were only followed for the first 90-120 days in the U.S. Recreational animals have been pinpointed as a high-risk source of cattle tuberculosis (Mycobacterium bovis) within the US, and maintaining animal identification throughout the production chain would benefit the U.S. in the event of an animal disease outbreak. This technology has the capability to bridge the gap between a Mexican identification system that allows herd of origin trace-back and the U.S. In order for the technology to be successful, new operators must be able to be trained to efficiently and capture retinal images in a timely manner that can be used for identity re-establishment. A field trial was conducted to compare the performance of two novice operators to an expert operator. Operator performance was measured by the time required to capture a retinal image and the match comparison score when an operators images were compared.
Keywords: Veterinary epidemiology -- Technological innovations; Animal marking -- Technological innovations